Exploring a combined Escherichia coli-based glycosylation and in vitro transglycosylation approach for expression of glycosylated interferon alpha. (1st March 2021) - Prabhu, Sunaina Kiran; Yang, Qiang; Tong, Xin; Wang, Lai-Xi
Graphical abstract: Two-step glycosylation of proteins using E. coli . Abstract: The conventional use of E. coli system for protein expression is limited to non-glycosylated proteins. While yeast, insect and mammalian systems are available to produce heterologous glycoproteins, developing an engineered E. coli -based glycosylation platform will provide a faster, more economical, and more convenient alternative. In this work, we present a two-step approach for production of a homogeneously glycosylated eukaryotic protein using the E. coli expression system. Human interferon α-2b (IFNα) is used as a model protein to illustrate this glycosylation scheme. In the first step, the N -glycosyltransferase from Actinobacillus pleuropneumoniae (ApNGT) is co-expressed for in vivo transfer of a glucose residue to IFNα at an NX(S/T) N -glycosylation sequon. Several E. coli systems were examined to evaluate the efficiency of IFNα N -glucosylation. In the second step, the N -glucosylated protein is efficiently elaborated with biantennary sialylated complex-type N -glycan using an in vitro chemoenzymatic method. The N -glycosylated IFNα product was found to be biologically active and displayed significantly improved proteolytic stability. This work presents a feasible E. coli -based glycosylation machinery for producing therapeutic eukaryotic glycoproteins.